Shaping Management in Gendered Work – A Comparative Study in the Swedish Public Sector - Forsberg, Tina; Härenstam, Annika (Scandinavian Journal of Public Administration, 2022)
By exploring management in a study of different municipal departments, this paper contributes to a theoretical and empirical understanding of how the type of work shapes and reproduces management practices and inequality in working conditions within a horizontally segregated public sector. A structural theoretical model guides the design of the empirical qualitative study within education, elderly care and water supply in several Swedish municipalities. The comparative analysis shows that, while managers within water supply take control over management and are allowed to do so, managers in education and care are instructed to take personal responsibility when handling goal conflicts and lack of resources. Gendered norms and values inscribed in the type of work seem to be fundamentally integral to management practices, which affect the local manager’s authority and actions. The results of this study illustrate how management is practiced and reinforces differences in status between different types of work.